Insights Into the Relationships Between Health Communication and Doctor-patient Relationship: A Scientometric Analysis Based on CiteSpace and Validation of Questionnaires - Renjie Lu PhD; Shenyu Zhao BD; Xiaoyu Wang BD; Jing Zhou BD; Weiyan Ou MD; Yongyi Jiang MD; Juan Wen PhD; Lingmin Hu PhD (SAGE Publishing, 2023)
In order to understand the research status of the relationship between health communication and doctor-patient relationship, and to explore a new path of the impact of health communication on doctor-patient relationship, this paper adopted qualitative methods to quantize the literature over the past 10 years in the Web of Science database and carried out Co-Authorship Analysis, Co-Citation Analysis and Co-Occurrence Analysis based on CiteSpace. In addition, according to the results of bibliometric research, self-designed questionnaires were used to verify the result. A convenience sampling survey was conducted through the online "Questionnaire Star" platform (https://www.wjx.cn) on May 8, 2022, and a total of 254 questionnaires were collected. Interviewees were asked to use social software to acquire health knowledge. Participants come from 21 provinces, 4 municipalities, and 4 autonomous regions across the country, which is geographically representative. The results show that uncertainty of social media information and the particularity of the epidemic make the research on health communication and doctor-patient relationship in social media become a new hot spot. Social media health information quality (source credibility and content trust perception), information asymmetry perception, doctor-patient communication, doctor-patient consistency, doctor-patient trust, doctor-patient relationship may be the key variables for constructing theoretical models.